USER EXPERIENCE ON IZAKAT KEDAH MOBILE APPLICATION: THE ZAKAT PAYERS’ PERSPECTIVE - Azizah Che Omar, Nurulnadwan Aziz, Mohd Adib Abd Muin, Subashini a/p Annamalai (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper reports an ongoing project related to the development of iZakatKedah mobile application. The developed prototype has been evaluated through expert review method. The results of the expert evaluation have been reported in the previous paper. Thus, the main aim of this paper is to test the user experience of iZakatKedah mobile application to the zakat payers in terms of user usefulness, ease of use, and ease of learning. There are 31 of zakat payers from Kedah State, Malaysia involves in the user experience experiment. Upon utilizes the iZakatKedah mobile application, a set of user experience questionnaires has been distributed to the respondents. The collected data were analyzed and presented in the form of descriptive statistics. The results reveal that most of the respondents agreed that the iZakatKedah mobile application is useful, easy to use, easy to learn, and overall, they are satisfied.